Hotspot‐Engineered 3D Multipetal Flower Assemblies for Surface‐Enhanced Raman Spectroscopy. (7th May 2014) - Jung, Kinam; Hahn, Jungsuk; In, Sungjun; Bae, Yongjun; Lee, Heechul; Pikhitsa, Peter V.; Ahn, Kwangjun; Ha, Kyungyeon; Lee, Jong‐Kwon; Park, Namkyoo; Choi, Mansoo
<x xml:space="preserve">Abstract</x> Novel 3D metallic structures composed of multipetal flowers consisting of nanoparticles are presented. The control of surface plasmon hotspots is demonstrated in terms of location and intensity as a function of petal number for uniform and reproducible surfaceenhanced Raman spectroscopy (SERS) with high field enhancement. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>